Outcome-based contracts – Linking technology, ownership and reputations. (June 2023) - Shanmugam, Ramesh Kumar; Dhingra, Tarun
Abstract: Outcome-based contracts (OBC) in information technology outsourcing have attracted much attention, but literature is relatively scarce on this topic. Though firm theories prefer hierarchy as the most protective form of governance for such transactions, the practice moves forward with many hybrid governance structures underpinned by automation and digital transformation technologies. The objective of this paper is to develop a conceptual framework that explains the preference for inter-firm arrangements in OBCs and exhibits the capabilities of these technologies in mitigating contract inefficiencies. The proposed framework narrows the gap in the literature for a concurrent view of the latitudinal (ex-post, ex-ante) and longitudinal (reputation) dimensions of the contract. We represent the OBC as a concurrent stochastic game in a probabilistic model checker. Testing of our propositions revealed that these technology assets are complementary and joint ownership is desirable under reputation effects, reputation transfers take place between the contracting parties in the same direction, and continuous reallocation of ownership is required to maintain joint ownership. Rapid technological advancement and industry maturity can gravitate the transaction towards common ownership. The reputation function using Fermi probability distribution in our model is a novel performance measure for the industry. Highlights: Integrates firm theories and reputation to unravel ex-ante and ex-post risks of OBCs. Leverages firm reputations and digital technology ownership in alleviating risks. Governance strategies to respond to technology, ownership and reputation evolution. Contract as concurrent stochastic games; Reputation as Fermi distribution function. Representation in probabilistic temporal logic and model checking in PRISM-games.